Nutrition therapy for chronic kidney disease - Thomas, Lynn K.; Thomas, Lynn K.; Bohnstadt Othersen, Jennifer (Boca Raton : CRC Press, 2012)
"This book presents variations in nutritional therapy through the five stages of chronic kidney disease. Chapters cover history of renal disease management and pathophysiology; electrolyte and acid-based disorders; acute renal disease; dialysis techniques; children/adolescents with chronic kidney disease; pregnancy with chronic kidney disease; bone and mineral disorders management; drug-nutrient/drug supplements; endocrine and lipid management; anemia management; enteral and parenteral support; nutrition post transplant; and establishing quality of life improvement parameters. The text links clinical applications to the Kidney Foundation Outcome Quality Initiative resources and provides dietary and supplement recommendations"--
Includes bibliographical references and index.
Keywords: Kidneys -- Diseases -- Nutritional aspects; Kidneys -- Diseases -- Diet therapy; MEDICAL / Nephrology; MEDICAL / Nutrition; MEDICAL / Public Health